The Absence of the World as Existential Terror in the Phenomenon of Digital Loneliness: The Perspective of Hannah Arendt - Panji Perdana Putra Priyanto; Ahmad Fatkhur Rohman; Galih Bayu Adam; Muhammad Alfin Hisam; Fuad Agil Fajri (GoAcademica Research & Publishing, 2026)
This study aims to reconceptualize the phenomenon of digital loneliness as an existential terror of worldlessness through Hannah Arendt’s philosophical framework. The contemporary cyberspace architecture driven by surveillance capitalism, creates a paradox where the illusion of hyper-connectivity leads to mass alienation and ontological isolation. Employing qualitative library research and philosophical hermeneutics on Arendt’s major works, this research traces the structural impacts of digital algorithms on human capacity for plural existence. Findings indicate that social media platforms do not facilitate authentic connection, they operate as a contemporary iron band of terror that systematically destroys the space of appearance and the common world. This algorithmic mechanization isolates individuals within echo chambers, amputates representative thinking, and plunges society into unreflective digital banality. The study concludes that digital loneliness is a manifestation of algorithmic totalitarianism that radically reduces individual existence. Therefore, emancipation from this atomization terror demands an ontological recovery. Transforming radical loneliness into reflective solitude and practicing the courage to stop and think as an absolute prerequisite to restore human dignity as social beings in a shared world.